Comparison of Physiological and Perceptional Responses to 5-m Forward, Forward-Backward, and Lateral Shuttle Running - Gao, Chong; Wang, Xiaolu; Zhang, Guochao; Huang, Li; Han, Mengyuan; Li, Bo; Nassis, George P.; Li, Yongming (Frontiers in Physiology, 2022)
Purpose: Shuttle running provide the possibility to stimulate the cardiorespiratory system in a limited space. However, the physiological and perceptional responses to different directional modes of shuttle running was unclear. The aim of this study was to investigate the physiological and perceptional responses to forward, forward-backward and lateral shuttle running. Methods: Twenty-four eligible male subjects performed a maximal oxygen uptake (VO2max) test and three directional modes (i.e., forward, forward-backward, and lateral) of 5-m shuttle running at the speed of 6 km·h-1 for 5 minutes on separate days. Heart rate (HR) and oxygen uptake (VO2) were continuously measured during the whole tests. Rating of perceived exertion (RPE) was inquired and recorded immediately after the test. Capillary blood samples were collected from the earlobe during the recovery to determine the peak value of blood lactate concentration ([La-]peak). Results: Running directional mode had significant effects on HR (F=72.761, P<0.001, η2p=0.760), VO2 (F=110.320, P<0.001, η2p=0.827), %VO2max (F=108.883, P<0.001, η2p=0.826), [La-]peak (F=55.529, P<0.001, η2p=0.707) and RPE (F=26.268, P<0.001, η2p=0.533). All variables were significantly different between conditions (P ≤ 0.017), with the variables highest in lateral shuttle running and lowest in forward shuttle running. The effect sizes indicated large magnitude in the differences of all variables between conditions (ES= 0.86 ~ 2.83, large) except the difference of RPE between forward and forward-backward shuttle running (ES= 0.68, moderate). Conclusion: These findings suggest that the physiological and perceptional responses in shuttle running at the same speed depended on the directional mode, with the responses highest in lateral shuttle running, and lowest in forward shuttle running.